Contact infection spread in an SEIR model: An analytical approach - Puntani Pongsumpun; Rujira Kongnuy; Diana Garca Lpez; I-Ming Tang; Marc A. Dubois (My University, 2013)
The epidemic spread of an SEIR (susceptible-exposed-infectious-recovered) model is analysed via a contact infection process.We solve the system of nonlinear partial differential equations by using the method of separation of variables.Approximate analytical expressions for the propagating infection wave for various ranges of parameters are presented.
Keywords: Mathematical and Theoretical Epidemiology and Ecology Models